Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/aos.13023
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ocular pressure fluctuation after cataract surgery in primary angle‐closure glaucoma eyes medically controlled after laser iridotomy

Abstract: Cataract surgery in PACG provides the opportunity to address many pathologies with one intervention; improving vision, diminishing IOP, blunting IOP fluctuation, reducing need for medications, eliminating a narrow angle and improving GQL-15 scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Very wide variations have been reported in IOP fluctuations post cataract surgery and a lot of research work has been conducted to establish relationship between the same. (19) (20) (21) (22) ( 23) (24) Our study was conducted to find out if uncomplicated phacoemulsification could be an alternative for IOP control.…”
Section: Resultsmentioning
confidence: 99%
“…Very wide variations have been reported in IOP fluctuations post cataract surgery and a lot of research work has been conducted to establish relationship between the same. (19) (20) (21) (22) ( 23) (24) Our study was conducted to find out if uncomplicated phacoemulsification could be an alternative for IOP control.…”
Section: Resultsmentioning
confidence: 99%
“…4,7,[37][38][39][40][41] Whether clear or cataracted, a thicker lens, [41][42][43][44][45][46] a more anteriorly positioned lens, or a lens with a higher vault, [46][47][48] can contribute to a shallower anterior Many studies demonstrated the benefits of phacoemulsification in the management of PACG. 16,17,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Phacoemulsification results in IOP reduction comparable to that following trabeculectomy or phacotrabeculectomy with significantly fewer complications. [14][15][16][17] However, those undergoing phacotrabeculectomy can have marginally lower IOP and less dependence on IOP lowering medications than those having phacoemulsification alone, which can be beneficial in patients with advanced PACG or poor medication compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Lens extraction reduces diurnal IOP fluctuations, IOP levels and the number of anti glaucoma medication in PACG with previous laser iridotomy, the change in IOP fluctuation values correlates positively with the change in anterior chamber deep an preoperative IOP fluctuation [38]. Thus patients with narrowest angles might experience a greater benefit from cataract surgery alone depending on the proportion of the angle that has been permanently closed by peripheral anterior synechiae.…”
Section: Cataract Surgery and Angle-closure Glaucomamentioning
confidence: 99%